ROLE OF CERTAIN GROWTH FACTORS IN INSULIN RESISTANCE IN A SAMPLE OF IRAQI OBESE PATIENTS WITH TYPE 2 DIABETES MELLITUS ISRAA MUHAMMAD MUBARAK ALDOURI, JABBAR HAMEED YENZEEL - Al-Douri, Israa Muhammad Mubarak; Yenzeel, Jabbar Hameed (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Background: Obesity and type 2 diabetes mellitus (T2DM) are closely interconnected metabolic disorders, with insulin resistance representing a key underlying mechanism. Growth factors such as fibroblast growth factor-21 (FGF21) and transforming growth factor-beta (TGF-β) have been increasingly implicated in metabolic dysregulation; however, their roles in obese Iraqi patients remain insufficiently explored. Methods: This cross-sectional study included 100 participants divided into three groups: obese patients with T2DM (n=35), obese non-diabetic individuals (n=35), and healthy controls (n=30). Clinical and biochemical parameters, including body mass index (BMI), fasting blood glucose (FBG), and glycated hemoglobin (HbA1c), were measured. Serum levels of FGF21 and TGF-β were determined using enzyme-linked immunosorbent assay (ELISA). Statistical analysis was performed using SPSS, with significance set at p<0.05. Results: Significant increases (p≤0.01) in FBG and HbA1c were observed in the obese with T2DM group compared to other groups. Serum FGF21 and TGF-β levels were significantly elevated in obese patients with T2DM (795.92±126.22 pg/ml and 2360.25±204.51 pg/ml, respectively) compared to controls. No significant differences were observed between obese non-diabetic and control groups. These findings indicate progressive metabolic deterioration associated with insulin resistance. Conclusion: Elevated FGF21 and TGF-β levels are strongly associated with obesity complicated by T2DM and may reflect underlying metabolic stress, inflammation, and fibrosis. These growth factors could serve as potential biomarkers for insulin resistance and disease progression in obese individuals.